Cytotoxicity and biocompatibility of Zirconia (Y-TZP) posts with various dental cements - Hyeongsoon Shin; Hyunjung Ko; Miri Kim (Korean Academy of Conservative Dentistry, 2016)
Objectives Endodontically treated teeth with insufficient tooth structure are often restored with esthetic restorations. This study evaluated the cytotoxicity and biological effects of yttria partially stabilized zirconia (Y-TZP) blocks in combination with several dental cements. Materials and Methods Pairs of zirconia cylinders with medium alone or cemented with three types of dental cement including RelyX U200 (3M ESPE), FujiCEM 2 (GC), and Panavia F 2.0 (Kuraray) were incubated in medium for 14 days. The cytotoxicity of each supernatant was determined using 3-(4,5-dimethylthiazole-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assays on L929 fibroblasts and MC3T3-E1 osteoblasts. The levels of interleukin-6 (IL-6) mRNA were evaluated by reverse transcription polymerase chain reaction (RT-PCR), and IL-6 protein was evaluated by enzyme-linked immunosorbent assays (ELISA). The data were analyzed using one-way ANOVA and Tukey post-hoc tests. A p < 0.05 was considered statistically significant. Results The MTT assays showed that MC3T3-E1 osteoblasts were more susceptible to dental cements than L929 fibroblasts. The resin based dental cements increased IL-6 expression in L929 cells, but reduced IL-6 expression in MC3T3-E1 cells. Conclusions Zirconia alone or blocks cemented with dental cement showed acceptable biocompatibilities. The results showed resin-modified glass-ionomer based cement less produced inflammatory cytokines than other self-adhesive resin-based cements. Furthermore, osteoblasts were more susceptible than fibroblasts to the biological effects of dental cement.